Eğitim Yöneticilerinin Bireysel Girişkenlik ve Etkin İletişim Davranışlarının Öğretmenlerin Dağıtık Liderlik Algısına Etkisi / The Effect of Individual Assertiveness and Effective Communication Behaviors of Education Managers on Distributed Leadership Perception of Teachers - Osman Bayraktar (Tarih Kültür ve Sanat Araştırmaları Dergisi, 2018)
Abstract Distributed leadership is a management approach that found itself an application field especially in educational institutions. In the research, the effect of self-assertiveness and effective communication behaviors on the distributed leadership perception in an educational institution that is a lifelong learning center is expected to be specified and how this effect changes according to seniority and education factors is tried to be determined.